Proposição de metodologia de análise da influência de um corpo d'água na paisagem sonora urbana: estudo de caso na cidade de Piracicaba - SP - Fernandes, Maria Eugênia (Universidade Federal de São Carlos, 2024)
Growing urbanization contributes to health problems, with noise pollution, mainly caused by traffic noise, being a major nuisance leading to disturbances, including sleep disorders. Research on soundscapes that considers the context and user perception has improved urban acoustic quality, especially due to the masking potential of positive sound sources over traffic noise. This research proposes a methodology to analyze the influence of bodies of water on the urban soundscape through sound pressure level measurements and user perception evaluations around an urban river in Piracicaba-SP, considering seasonal variations in water flow. Questionnaires were administered to assess user perception and to calculate acoustic and psychoacoustic parameters. The main sound sources identified were water, traffic, and birdsong. The sound levels at the evaluated points are above the ABNT NBR 10151 standard limit, but only at the point with intense traffic does this result coincide with user perception. Although respondents perceive differences at points with intense traffic, tolerance was high at all points, even with elevated sound pressure levels. Seasonal variations influence the perception of comfort, tolerance, and pleasantness, being more positive during the dry season. However, at points with intense and moderate traffic, negative perceptions were mitigated during the wet season. Hearing more water sounds is associated with more positive sound environments. Thus, the research confirms the hypothesis that natural sounds improve soundscape quality and increase user tolerance to the urban sound environment.
Proposal of a methodology for analyzing the influence of a body of water on the urban soundscape: a case study in the city of Piracicaba - SP
Keywords: Paisagem sonora; Sons de água; Fontes sonoras positivas; Mascaramento; Psicoacústica; Soundscape; Water sounds; Positive sound sources; Masking; Psychoacoustics; ENGENHARIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL::TECNICAS DE ANALISE E AVALIACAO URBANA E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL::TECNICAS DE PLANEJAMENTO E PROJETO URBANOS E REGIONAIS; OUTROS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::TECNOLOGIA DE ARQUITETURA E URBANISMO::ADEQUACAO AMBIENTAL